Finite element analysis of stress in the equine proximal phalanx. (4th September 2012) - O'Hare, L. M. S.; Cox, P. G.; Jeffery, N.; Singer, E. R.
Summary Reasons for performing study To improve understanding of the internal structure of the proximal phalanx (P1), response of the bone to load and possible relation to the pathogenesis of fractures in P1. Objectives To model the P1 and replicate the loads experienced by the bone in stance, walk, trot and gallop using finite element analysis. Methods The geometry of the P1 was captured using micro‐computed tomography (μCT) and was reconstructed in 3 dimensions. Values for material properties and forces experienced at stance, walk, trot and gallop were taken from the literature and were applied to the reconstructed model. Using the same total load across the proximal articular surface, the model was solved with and without loading of the sagittal groove. Biomechanical performance was then simulated with finite element analysis and evaluated in terms of von Mises stress maps. Results Compared with the lowest force simulation equivalent to stance, the effects of the gallop force showed higher levels of stress along the sagittal groove and on the palmar surface just distal to the sagittal groove in both models, with and without the sagittal groove loaded. The results highlighted an area of bone on the dorsal aspect of P1 that experiences lower stress compared with the rest of the dorsal surface, an effect that was much more apparent when the sagittal groove was not loaded. Qualitative comparison of the models revealed minimal difference in the pattern of von Mises stress between the loaded and unloaded groove models. Conclusions The study demonstrates a finite element model of P1 that produces results consistent with clinical observation. The simulated high stress levels associated with the sagittal groove correspond to the most common site for fractures in the equine P1. Potential relevance With refinement of the model and further investigation, it may be possible to improve understanding of the behaviour of P1 under loading conditions that more closely simulate those experienced in the living animal, leading to a more solid understanding of fractures of P1.